1996
DOI: 10.1542/peds.98.4.706
|View full text |Cite
|
Sign up to set email alerts
|

Four Patterns of Response to Inhaled Nitric Oxide for Persistent Pulmonary Hypertension of the Newborn

Abstract: Objective. To determine the clinical role of inhaled nitric oxide (iNO) in the treatment of persistent pulmonary hypertension of the newborn (PPHN). Study Design. Prospective open observational clinical study. Setting. A regional cardiac and pediatric intensive care unit. Methods. Twenty-five consecutive near-term neonates (>35 weeks gestation) with severe PPHN (oxygenation index [OI]> 25) were given a trial of iNO of 20 ppm for 20 minutes. Neonates wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Thus, some of the neonates who were labeled as non-responders in our study may have had a late response to iNO. Alternatively, it is documented that some neonates who have an initial response to iNO fail to sustain that response over time [27,33,34], and this may have been the case in some of our patients who were labeled as responders. Some studies classified any neonate who required ECMO during the hospitalization as iNO non-responsive [8].…”
Section: Discussionmentioning
confidence: 86%
“…Thus, some of the neonates who were labeled as non-responders in our study may have had a late response to iNO. Alternatively, it is documented that some neonates who have an initial response to iNO fail to sustain that response over time [27,33,34], and this may have been the case in some of our patients who were labeled as responders. Some studies classified any neonate who required ECMO during the hospitalization as iNO non-responsive [8].…”
Section: Discussionmentioning
confidence: 86%
“…Inhaled nitric oxide selectively reduces PVR; however, there are data suggesting approximately 30% of patients with PPHN are non-responders. 14 Sildenafil and milrinone reduce PVR via their actions as phosphodiesterase 5 and 3 inhibitors, respectively. However, their effects on SVR can induce systemic hypotension and decreased end organ perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, theoretically, NO can effectively prevent or treat BPD. Clinically, NO has been shown to be a specific drug for improving short-term oxygenation in neonates and a treatment for persistent pulmonary hypertension ( Goldman et al, 1996 ; Dani et al, 2017 ). A meta-analysis showed that iNO improved short-term oxygenation and decreased ECMO use in term or near-term infants ( Barrington et al, 2017a ).…”
Section: Introductionmentioning
confidence: 99%